Comparative Study of the Fit Accuracy of Full-Arch Bar Frameworks Fabricated with Different Presintered Cobalt-Chromium Alloys. - Mai, Hang-Nga; Kwon, Tae-Yub; Hong, Min-Ho; Lee, Du-Hyeong (BioMed Research International, 2018)
Purpose. This study was to measure the geometric discrepancies that occur during the sintering contraction of presintered Co-Cr alloys in a full-arch bar framework and to compare the variations between alloys from different manufacturers. Materials and Methods. Eighteen implant-supported full-arch bar frameworks were fabricated through a soft-machining process using presintered Co-Cr alloy blocks: Ceramill Sintron (CS), Soft Metal (SM), and Sintermetall (SML) (n=6 for each group). The sintered frameworks were digitized using a structured light scanner, and the scan images were superimposed on the reference design. The geometric discrepancies of the sintered frameworks were three-dimensionally analyzed for horizontal, angular, and internal discrepancies. Kruskal-Wallis and Mann–Whitney U tests were used to compare the discrepancies among the groups (α=.05). Results. Significant differences were found in the geometric discrepancy measurements among the groups. The CS group showed larger horizontal and angular discrepancies, followed by the SM and SML groups (P<.001). The root mean square (RMS) values for internal discrepancy were not statistically different among the groups (P=.778). Conclusion. The geometric discrepancies of full-arch bar frameworks fabricated using the soft-machining process were affected by accuracies in sintering contraction of presintered alloys.